Health service utilization for low back pain in Germany between 2000 and 2020—a scoping review of claims data - Truthmann, Julia; Kiel, Simone; Vrana, Georg; Chenot, Jean-François (Frontiers in Pain Research, 2025)
BackgroundLow back pain (LBP) uses a large proportion of health care resources. Data are needed for health care planning, measuring adherence to guidelines for quality assurance, and assessing overuse and underuse of health care services. The aim of this review is to summarize claims data and describe trends in health care utilization for LBP for the years 2000 to 2020.MethodsThis scoping review summarizes studies and health reports using claims data of people aged ≥15 years covered by a statutory health insurance in Germany for the period 2000 to 2020. We searched publications in PubMed, EMBASE and Google. Data on health care services were extracted and trends over the years were summarized.ResultsWe included data from 76 publications, health reports and online databases. Every year, 25 to 32% of adults in Germany seek care for LBP. Most of the claims data cannot be pooled because of differences in standardization and reporting. However, trends are observable. Magnetic resonance imaging increased to 7.5%, plain radiography decreased to 15%. The number of sick leave days decreased slightly over time. Hospital admissions for LBP, spinal surgery, and opioid use increased. Outpatient rehabilitation increased, but the overall use of rehabilitation services remained relatively stable.ConclusionsInconsistent reporting standards and fragmentation of German claims data reporting, hinders a comprehensive understanding of health service utilization for low back pain. Despite limitations, current data suggest potential overuse of resources for LBP in Germany, consistently with international data. Given the high proportion of patients consulting for LBP better monitoring of health service utilization is needed to improve quality of care and resource allocation.